Hubungan Dukungan Sosial, Beban Belajar, Kecerdasan Emosional, Kejenuhan, dan Prestasi Belajar Matematika - Sarwo Edy; Syaiful Huda; Pratama Maulana Putra (Jurnal Pendidikan Indonesia, 2024)
Social support, learning burden, emotional intelligence, and student learning boredom are things that students experience psychologically when learning mathematics. This study aims to analyze the relationship between social support and learning burden, emotional intelligence, learning boredom, and students' mathematics learning achievement. This study uses a survey research design. The subjects of the study were junior high school students with a sample size of 377 from a population of 6,658. The study sample was 377 students, obtained from a total population of 6658 students, using the area proportional simple random sampling technique. Data collection will be done using a questionnaire to determine the relationship. Data analysis techniques using Structural Equation Modeling (SEM), consisting of measurement models and structural models through the Analysis of Moment Structure (AMOS) program, were used to analyze the data obtained. The results of the study showed that social support had an effect on learning burden, emotional intelligence, learning boredom, and mathematics learning achievement; learning burden had an impact on learning boredom; emotional intelligence had an effect on learning burden and learning boredom. The conclusion of the study shows that the relationship between social support, learning burden, emotional intelligence, boredom, and mathematics learning achievement are interrelated. The implications of this study provide information to teachers and educators that social support for students affects student learning achievement.